Peran Pendidikan Karakter dalam Kurikulum Merdeka terhadap Perilaku Etika dan Moral Siswa Generasi Z: Penelitian - Sudirman, Sahrun; Ajam, Ali; Safrudin Sahmadan; Ahmad, Mahdi; Wahid, Afidaa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of Generation Z living in the digital era presents new challenges in shaping students' ethical and moral behavior. The Independent Curriculum was designed in response to the needs of 21st-century education by placing character education as the main foundation through strengthening the Pancasila Student Profile. This study aims to analyze the role of character education in the Independent Curriculum on the ethical and moral behavior of Generation Z students. The research method used is a qualitative approach with a literature study of scientific journals, educational policy documents, and relevant previous research results. The results of the study indicate that character education in the Independent Curriculum plays a significant role in shaping students' ethical and moral behavior through the integration of character values ​​in learning, project-based learning, and teacher role models. However, the implementation of character education still faces challenges in the form of educator readiness and the influence of the digital environment. This study concludes that character education in the Independent Curriculum contributes positively to the ethical and moral formation of Generation Z students if implemented consistently and collaboratively.